In situ hydrodeoxygenation upgrading of pine sawdust bio-oil to hydrocarbon biofuel using Pd/C catalyst. Issue 2 (April 2018) - Cheng, Shouyun; Wei, Lin; Alsowij, Mustafa Radhi; Corbin, Fletcher; Julson, James; Boakye, Eric; Raynie, Douglas
Abstract: Hydrodeoxygenation (HDO) is effective for upgrading bio-oil to biofuel. However, the upgrading cost increased due to the high consumption of external hydrogen. In this paper, the hydrogen generated from cheap water using zinc hydrolysis for in situ bio-oil HDO was reported. The effect of different temperatures (200 °C, 250 °C and 300 °C) on bio-oil HDO over Pd/C catalyst was investigated in a batch reactor. The results show that 250 °C yielded biofuel with the highest heating value at 30.17 MJ/kg and the highest hydrocarbons content at 24.09%. Physicochemical properties including heating value, total acid number and chemical compositions of the produced biofuels improved significantly in comparison with that of the original bio-oil. Highlights: In situ bio-oil HDO was conducted via integrated zinc hydrolysis and Pd/C catalysis. 250 °C treatment produced biofuel with highest hydrocarbons content. Properties of biofuels (water content, TAN and HHV) improved significantly. Acids, aldehydes, ketones and phenols contents decreased significantly in biofuels.